Endoscopic features and genetic background of inflammatory bowel disease complicated with Takayasu arteritis. Issue 5 (27th April 2017) - Akiyama, Shintaro; Fujii, Toshimitsu; Matsuoka, Katsuyoshi; Yusuke, Ebana; Negi, Mariko; Takenaka, Kento; Nagahori, Masakazu; Ohtsuka, Kazuo; Isobe, Mitsuaki; Watanabe, Mamoru
Abstract: Background and Aim: Takayasu arteritis (TA) is occasionally complicated with inflammatory bowel disease (IBD). This study assessed the endoscopic and genetic features of IBD complicated with TA (IBD‐TA). Methods: This study retrospectively reviewed the clinical charts of 142 TA patients (14 men and 128 women; median age 48.5 years [range, 18–97 years]). Human lymphocyte antigen (HLA) types and a single‐nucleotide polymorphism rs6871626 in the IL12B gene were assessed in 101 and 81 patients with TA, respectively. Results: Inflammatory bowel disease was diagnosed in 13 (9.2%) of the 142 patients. The endoscopic features of IBD‐TA at initial diagnosis ( n  = 8) showed discontinuous and focal mucosal inflammations ( n  = 7, 87.5%), and only one case was diagnosed as ulcerative colitis (UC) at the first colonoscopy. In the genetic comparison of HLA class I between TA patients with IBD and those without IBD, HLA‐B*52:01 and C*12:02 were more frequent in the IBD‐TA group ( P  = 0.001 and P  = 0.009, respectively). Meanwhile, HLA‐DRB‐1*15:02, DQA‐1*01:03, DQB‐1*06:01, and DPB‐1*09:01 as HLA class II were positively associated with IBD‐TA ( P  = 0.004, P  = 0.019, P  = 0.019, and P  = 0.002, respectively). IL12B rs6871626 did not show an association with IBD‐TA compared with that with TA without IBD. Conclusions: The endoscopic findings of IBD‐TA at initial diagnosis were atypical for UC or Crohn's disease. IBD‐TA possessed the HLA haplotype, which had a susceptible effect on UC.